PEMBUATAN GAME IMPOSSIBLE PLATFORMER "MY UNFAIR ADVENTURE" PADA ANDROID - Kevin Alexander; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
This game was created using the Unity game engine with C# as its programming language. The goal of this game is to complete all the stages. At each stage, players will face various obstacles such as monsters, traps, and hazards. Testing is done by blackbox testing, alpha testing by the supervisor, and beta testing by 32 respondents through a questionnaire. The test results show that the game My Unfair Adventure can make players annoyed but still encourage them to play again.